Assessing pH‐dependent activities of virulence factors secreted by Candida albicans. Issue 1 (3rd January 2023) - Ramos‐Pardo, Asier; Castro‐Álvarez, Rocío; Quindós, Guillermo; Eraso, Elena; Sevillano, Elena; Kaberdin, Vladimir R.
Abstract: Candida albicans is an opportunistic pathogen that can thrive under adverse conditions including suboptimal pH, nutrient scarcity, and low levels of oxygen. Its pathogenicity is associated with the production of virulence factors such as extracellular hydrolytic enzymes and toxins. This study was aimed at determining the effect of external pH, substrate nature, and strain origin on protease, lipase, and hemolysin production. To achieve this objective, agar plate assays were performed at pH 5.0, 6.5, and 7.5 with substrates suitable for the detection of each family of enzymes. Moreover, the study was conducted with 20 clinical C. albicans isolates from blood, oral cavity, skin, urine, and vagina. The hydrolytic zones formed around the colonies were further measured to calculate the Ez (enzymatic zone) indexes. We found that detection of proteases in skim milk agar plates was possible for most isolates only at pH 5 (80%) and pH 6.5 (75%), whereas BSA plates could confer protease detection exclusively at pH 5 (80%). Similarly, the percentage of isolates possessing lipolytic activities was higher at pH 5 (90%) than at pH 6.5 (70%) and pH 7.5 (35%). In contrast, hemolytic activities were detected in all isolates at pH 6.5 and 7.5 but not at pH 5. Further analysis revealed that some differences in the detected activities could potentially be attributed to the anatomical origin of these isolates. Collectively, these findings suggest that the pH of the site of infection might be critical for mimicking the microenvironment employed to experimentally discover the key virulence factors. Abstract : The pathogenicity of Candida albicans is associated with the production of virulence factors such as extracellular hydrolytic enzymes and toxins. The results reported here demonstrate that the activity of secreted hydrolytic enzymes, in particular proteases, lipases, and hemolysins, is generally dependent on pH and is potentially associated with the clinical origin of C. albicans isolates.